2022
DOI: 10.1111/nan.12816
|View full text |Cite
|
Sign up to set email alerts
|

Activating ATF6 in spinal muscular atrophy promotes SMN expression and motor neuron survival through the IRE1α‐XBP1 pathway

Abstract: Aim: Spinal muscular atrophy (SMA) is a neuromuscular disease caused by survival of motor neuron (SMN) deficiency that induces motor neuron (MN) degeneration and severe muscular atrophy. Gene therapies that increase SMN have proven their efficacy but not for all patients. Here, we explored the unfolded protein response (UPR) status in SMA pathology and explored whether UPR modulation could be beneficial for SMA patients.Methods: We analysed the expression and activation of key UPR proteins by RT-qPCR and by we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…In this respect, it is worth noticing that to observe cellular stress in hiPSC-derived MNs, it usually takes culture times longer than 25 days. Such UPR activation is rarely observed in hiPSC-derived MNs after only 25 days of culture as recently described in SMA hiPSC-derived MNs [ 8 ]. Finally, reduced MN survival in co-cultures and not in mono-cultures could be indicative of non-cell-autonomous mechanisms.…”
Section: Discussionmentioning
confidence: 71%
“…In this respect, it is worth noticing that to observe cellular stress in hiPSC-derived MNs, it usually takes culture times longer than 25 days. Such UPR activation is rarely observed in hiPSC-derived MNs after only 25 days of culture as recently described in SMA hiPSC-derived MNs [ 8 ]. Finally, reduced MN survival in co-cultures and not in mono-cultures could be indicative of non-cell-autonomous mechanisms.…”
Section: Discussionmentioning
confidence: 71%
“…3 online resource). Given that LARGE1 (acting as a bifunctional glycosyltransferase with both alpha-1,3-xylosyltransferase and beta-1,3-glucuronyltransferase activities) is localized to the ER-Golgi network and other ER-Golgi resident proteins were already unveiled as critical factors for motor neuron survival in SMA [ 5 ] and other motor neuron diseases such as ALS [ 10 ], were selected this protein as promising candidate for further analyses. This decision was also motivated by the known role of LARGE1 in the genesis of neuromuscular diseases (MIM: 608,840 & MIM:613,154).…”
Section: Resultsmentioning
confidence: 99%
“…19 From this screen, N-(2-hydroxy-5-methylphenyl)-3-phenylpropanamide (AA147; Fig 1A) emerged as a selective ATF6 activator that is able to promote adaptive ATF6 activity to mitigate pathologies associated with etiologically diverse disorders. 11,[19][20][21][22][23][24][25][26] We found that AA147 functions as a prodrug, wherein oxidative conversion of the 2-amino-p-cresol substructure by ER-resident oxidases (e.g., cytochrome P450s) leads to an electrophilic quinone methide and selective covalent engagement of a subset of ER proteins primarily consisting of protein disulfide isomerases (PDIs). 27 PDIs maintain ATF6 in disulfide-bonded structures that limit its activation.…”
Section: Introductionmentioning
confidence: 99%